Screening for hearing, visual and dual sensory impairment in older adults using behavioural cues: A validation study. - Roets-Merken, Lieve M.; Zuidema, Sytse U.; Vernooij-Dassen, Myrra J. F. J.; Kempen, Gertrudis I. J. M. (International Journal of Nursing Studies, 2014)
Objective: This study investigated the psychometric properties of the Severe Dual Sensory Loss screening tool, a tool designed to help nurses and care assistants to identify hearing, visual and dual sensory impairment in older adults. Design: Construct validity of the Severe Dual Sensory Loss screening tool was evaluated using Crohnbach's alpha and factor analysis. Interrater reliability was calculated using Kappa statistics. To evaluate the predictive validity, sensitivity and specificity were calculated by comparison with the criterion standard assessment for hearing and vision. The criterion used for hearing impairment was a hearing loss of ≥40 decibel measured by pure-tone audiometry, and the criterion for visual impairment was a visual acuity of ≤ 0.3 diopter or a visual field of ≤0.3°. Feasibility was evaluated by the time needed to fill in the screening tool and the clarity of the instruction and items. Prevalence of dual sensory impairment was calculated. Results: A total of 56 older adults receiving aged care and 12 of their nurses and care assistants participated in the study. Crohnbach's alpha was 0.81 for the hearing subscale and 0.84 for the visual subscale. Factor analysis showed two constructs for hearing and two for vision. Kappa was 0.71 for the hearing subscale and 0.74 for the visual subscale. The predictive validity showed a sensitivity of 0.71 and a specificity of 0.72 for the hearing subscale; and a sensitivity of 0.69 and a specificity of 0.78 for the visual subscale. The optimum cut-off point for each subscale was score 1. The nurses and care assistants reported that the Severe Dual Sensory Loss screening tool was easy to use. The prevalence of hearing and vision impairment was 55% and 29%, respectively, and that of dual sensory impairment was 20%. Conclusions: The Severe Dual Sensory Loss screening tool was compared with the criterion standards for hearing and visual impairment and was found a valid and reliable tool, enabling nurses and care assistants to identify hearing, visual and dual sensory impairment among older adults.